Acceptability, perceived outcomes and underlying mechanisms of a professionally led support group intervention for women with breast cancer using a qualitative method approach - Andreia Soares; Diogo Carreiras; Bruna Veloso; Ana Pereira; Priscyla Costa; Helena Moreira; Inês A. Trindade (British Journal of Health Psychology, 2026)
Abstract Objectives Breast cancer (BC) remains the most diagnosed cancer among women worldwide and its growing survivorship population faces numerous long‐term physical and psychological challenges. Cancer support groups emerge as promising interventions to promote comprehensive management of the disease and survivorship needs, emotional well‐being and social connection. Accordingly, this study aimed to analyse the acceptability and perceived impact of the Mind Support Group (MSG), a professionally led support group intervention designed for women with BC. Design A qualitative methodological approach was used to collect and analyse data. Methods Participants' feedback data were collected through a guided feedback discussion during the MSG final session and analysed using content and thematic analysis. Results The sample comprised 22 women diagnosed with BC (stages I–III). Findings showed high acceptability, with participants expressing satisfaction with several aspects of the intervention: interpersonal processes, content, group composition and perceived outcomes. Suggestions for improvement focused exclusively on the intervention dose (e.g., earlier access) and format (e.g., in‐person delivery). Mechanisms of change and perceived outcomes also emerged from participants' feedback. Through social (e.g., shared information and experience), behavioural (e.g., self‐disclosure) and psychological (e.g., emotional tension release) mechanisms, the MSG appeared to facilitate shifts toward more adaptive coping strategies, personal growth, a reduction in perceived isolation and alienation, and improved communication and self‐management skills. Conclusions These findings suggest that the MSG may serve as a valuable complement to medical treatment or, at minimum, inform the design of more comprehensive cancer care interventions integrating psychosocial support across the illness trajectory. Trial Registration NCT05642897; NCT06212414.